Risk-oriented geoinformation airspace modeling for calculating civil aviation unmanned aerial vehicles optimal routes - S. E. Maksimova (Научный вестник МГТУ ГА)
Currently, there is an urgent need to create a high-quality automated risk assessment tool for the use of (unmanned aircraft) UAVs. There is no universal approach to risk management in unmanned civil aviation, and the risk assessment of the operator is largely individual. At the moment, no tool has been developed for plotting optimal routes for UAV flights in airspace, which would avoid piloting in areas with unacceptable risk. The article suggests the use of fully functional geographic information systems (GIS) to assess the risks of performing a flight mission. For a qualitative assessment of the risks of a particular flight assignment, it is proposed to take into account the situational component in the relevant segment of airspace and the ground (surface) situation. The article systematizes the main groups of factors that are important for assessing the risks of using BV. UAV flights are exposed to environmental factors, while posing a danger to surrounding objects. A formula for analyzing the spatial and temporal distribution of risk values in the airspace is derived. The minimum size of the simulation cell is proposed. A universal approach to assessing the risks of a UAV flight by various operators is substantiated, and a methodology for spatiotemporal analysis of the distribution of risk values based on the use of GIS is given. The results of the analysis of spatial and temporal information in the GIS environment make it possible to zone the airspace according to the degree of flight acceptability and build the optimal route outside areas with an increased risk of an aviation incident or accident. The developed spatio-temporal risk-oriented model can be used to support management decision-making in terms of building optimal routes for the movement of UVs.